2021
DOI: 10.1093/milmed/usab240
|View full text |Cite
|
Sign up to set email alerts
|

The Veterinary Treatment Facility as a Readiness Platform for Veterinary Corps Officers

Abstract: Introduction U.S. Army Veterinary Corps provides highly skilled and adaptive veterinary professionals to protect and improve the health of people and animals while enhancing readiness throughout the DOD. Army veterinarians must be trained and credentialed for critical tasks within the animal health and food protection missions across all components. The Veterinary Metrics Division in the U.S. Army Public Health Center’s Veterinary Services and Public Health Sanitation Directorate is responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The frequency of TDI in the MWD population is nearly double the frequency of TDI in pet populations. Military studies have documented the frequency of dental encounters compared to overall patient encounters but never enumerated the diagnosis of each encounter within the study sample ( 3 , 4 , 10 ). Results from pet population studies quantify TDI frequency anywhere between 14% and 27% with the most recent study reporting 26.2% ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of TDI in the MWD population is nearly double the frequency of TDI in pet populations. Military studies have documented the frequency of dental encounters compared to overall patient encounters but never enumerated the diagnosis of each encounter within the study sample ( 3 , 4 , 10 ). Results from pet population studies quantify TDI frequency anywhere between 14% and 27% with the most recent study reporting 26.2% ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The United States Army is the Department of Defense (DOD) lead service for veterinary services and is the only branch of the military that employs veterinarians to provide full-service care to military working dogs. A 2021 military study documented that the second most common condition encountered in MWDs presenting to Army veterinary services in the United States was dental related conditions ( 3 ). This study also identified from 2014 to 2015 the most common primary encounter category to receive Army veterinary services for MWDs in Afghanistan was dental, followed by surgical, soft-tissue injury, dermatology, and musculoskeletal.…”
Section: Introductionmentioning
confidence: 99%